Selecting a Network Media for sharing E- Resources A Comparative Learning Report - Ketheeswaren, S.; Prabu, R.; Rosaline Mary, S.; Visvanath, B. (CALIBER 2009, 2009)
Transmission media are the physical pathways (guided or unguided) that connect computers, other devices, and people on a network. Computers and telecommunication devices use signals to represent data. These signals are transmitted from a device to another in the form of electromagnetic energy. Examples of Electromagnetic energy include power, radio waves, infrared light, visible light, ultraviolet light, and X and gamma rays. All these electromagnetic signals constitute the electromagnetic spectrum. Each portion of the spectrum requires a particular or unique transmission media for the transfer of data such we call as Twisted Pair, Coaxial cable, Optical fibber, Satellite, and Wireless etc. In the paper, The Guided (Twisted Pair, Coaxial cable, Optical fiber) and the Unguided Microwaves (Satellite, wifi, wimax, bluetooth) transmission mediums are compared with help of relative plots in terms of their networking capabilities (e.g., speed, damping length, Bandwidth, Cost and Get connection). Optical fibber in the guided media outperforms other medias in better networking performance but optical fibber cable connection is sensitive than twisted Pair and Coaxial cable connections and require higher cost that the same. Twisted pair outperforms coaxial cable. Here it is also notable that coaxial cable can be connected easily without order, but twisted pair not like that. Among Unguided; wimax outperforms other medias in better networking performance in long range even though wi-fi is a substitute for providing a greater power of access than wimax in short range. Here all unguided mediums are better for ease of access than guided.